Clinical application of a template‐guided automated planning routine. Issue 3 (8th November 2022) - Schmidt, Matthew C.; Abraham, Christopher D.; Huang, Jiayi; Robinson, Clifford G.; Hugo, Geoffrey; Knutson, Nels C.; Sun, Baozhou; Raranje, Chipo; Sajo, Erno; Zygmanski, Piotr; Jandel, Marian; Szentivanyi, Peter; et al.
Abstract: Purpose: Determine the dosimetric quality and the planning time reduction when utilizing a template‐based automated planning application. Methods: A software application integrated through the treatment planning system application programing interface, QuickPlan, was developed to facilitate automated planning using configurable templates for contouring, knowledge‐based planning structure matching, field design, and algorithm settings. Validations are performed at various levels of the planning procedure and assist in the evaluation of readiness of the CT image, structure set, and plan layout for automated planning. QuickPlan is evaluated dosimetrically against 22 hippocampal‐avoidance whole brain radiotherapy patients. The required times to treatment plan generation are compared for the validations set as well as 10 prospective patients whose plans have been automated by QuickPlan. Results: The generations of 22 automated treatment plans are compared against a manual replanning using an identical process, resulting in dosimetric differences of minor clinical significance. The target dose to 2% volume and homogeneity index result in significantly decreased values for automated plans, whereas other dose metric evaluations are nonsignificant. The time to generate the treatment plans is reduced for all automated plans with a median difference of 9′ 50″ ± 4′ 33″. Conclusions: Template‐based automated planning allows for reduced treatment planning time with consistent optimization structure creation, treatment field creation, plan optimization, and dose calculation with similar dosimetric quality. This process has potential expansion to numerous disease sites.